Photocuring of 4-arm coumarin-functionalised monomers to form highly photoreversible crosslinked epoxy coatings. Issue 17 (29th March 2019) - Hughes, T.; Simon, G. P.; Saito, K.
Abstract : Highly photoreversible photocurable crosslinked epoxy coatings that can heal substantial surface damage were formed by the synthesis of unique monomers. Abstract : Highly photoreversible and photocurable epoxy-based network polymers suitable for coating applications were produced by the synthesis of two coumarin-functionalised monomers. Three polymers were formed from the synthesised monomers: two of which are the monomers polymerised separately, with the third being a polymerised mixture of a 50 mol% blend of the two monomers. Through the irradiation with 365 nm UV light, high strength crosslinked networks were formed that exhibited thermal and mechanical properties similar to common commercial coating materials. These photopolymers were also tested for their photoreversible nature in response to different wavelengths of UV light using several analytical techniques as well as characterised by studying their photoinduced solubility and examining their self-healing performance. These results demonstrated the ability to tune the polymer properties, such as self-healing ability, by the monomer content as the mixed polymer exhibited exceptional healing performance and mechanical properties.